SOIL MOISTURE DETECTION USING ELECTRICAL CAPACITANCE TOMOGRAPHY SENSOR (ECT) - MOHD FUAD, SITI NOR FARHANAH BINTI (Universiti Teknologi PETRONAS, 2012)
Soil moisture content determination is a common process in agriculture which needs sensors with high accuracy and compatibility with the environment. The available methods are described with attention given to the gravimetry measurement, lysimeters, neutron scattering, gamma absorption, time domain reflectometer, electrical resistance blocks, and electrical tomography sensors. Current technique used is time domain reflectometer which is convenient and reliable. However, this device is quite expensive and cannot provide clear view of moisture percentage distribution in soil. The proposed sensor which is using tomographic method, can visualize data using permittivity distribution. By using an array of sensors that are positioned around the pipe, it is possible to visualize the percentage of soil moisture. Electrical Capacitance Tomography (ECT) is comparatively low cost and capable to make measurements rapidly. The mechanism used in ECT is non-invasive, inert, and non-ionizing. The report consists of an introduction, problem statement, objectives, literature review and methodology used to solve the problem. It further looks into the obtained results with consistent discussion.